Respuesta :
Answer:
The answer is
[tex]10 \sqrt{7} [/tex]
Step-by-step explanation:
To solve the radicals make sure that they both have the same radical
That's
[tex]4 \sqrt{7} + 3 \sqrt{28} [/tex]
Simplify 3√28 in order to combine the radicals
We have
[tex]3 \sqrt{4 \times 7} = 3 \times \sqrt{4} \times \sqrt{7} [/tex]
[tex] = 3 \times 2 \times \sqrt{7} [/tex]
[tex] = 6 \sqrt{7} [/tex]
So we now have
[tex]4 \sqrt{7} + 6 \sqrt{7} [/tex]
Using the rules of surds
That's
[tex]x \sqrt{a } + y \sqrt{a} = (x + y) \sqrt{a} [/tex]
Simplify the expression
We have
[tex]4 \sqrt{7} + 6 \sqrt{7 } = (4 + 6) \sqrt{7} [/tex]
We have the final answer as
[tex]10 \sqrt{7} [/tex]
Hope this helps you
Answer:
Step-by-step explanation:
[tex]4\sqrt{7}+3\sqrt{28}=4\sqrt{7}+3\sqrt{2*2*7}\\\\\\ =4\sqrt{7}+3*2\sqrt{7}\\\\\\= 4\sqrt{7}+6\sqrt{7}\\\\\\=(4+6)\sqrt{7}\\\\\\ =10\sqrt{7}[/tex]